The Development of Organic Chemistry Teaching Materials on The Topic of Lipid Using Android STEM Based Approach - Handayani, Dewi; Winarni, Endang Widi; Sundaryono , Agus; Firdaus , M.Lutfi; Alperi, Muzanip Alperi (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The purpose of this study was to develop teaching materials for Organic Chemistry 2 by using an android-based STEM approach, analyze the readability of teaching materials and determine student learning outcomes. This research belongs to the R&D type of the Borg and Gall model. This research was starting from the research and information gathering stage, planning, developing the initial product format, validation testing, initial product revision, field testing, product revision of field test results. The research subjects were undergraduate students of Chemistry Education who took organic chemistry courses 2. The instruments in this research were a material expert validation questionnaire, media expert validation and evaluation test sheets. The results showed that the teaching materials developed were considered feasible by the material expert validators with a percentage score of 93.33% and media experts 95.67%. The data from the readability test of teaching materials averaged 92.38 with a very good category. Student learning outcomes pretest and posttest scores increased from 55.56 to 78.61, the N-gain value was 0.51875 in the medium category. Based on this, it can be concluded that organic chemistry 2 teaching materials using an android-based STEM approach are very feasible and can improve student learning outcomes.